2011
DOI: 10.5194/se-2-315-2011
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Ringwoodite-Perovskite transition on mantle convection in spherical geometry as a function of Clapeyron slope and Rayleigh number

Abstract: Abstract. We investigate the influence on mantle convection of the negative Clapeyron slope ringwoodite to perovskite and ferro-periclase mantle phase transition, which is correlated with the seismic discontinuity at 660 km depth. In particular, we focus on understanding the influence of the magnitude of the Clapeyron slope (as measured by the Phase Buoyancy parameter, P ) and the vigour of convection (as measured by the Rayleigh number, Ra) on mantle convection. We have undertaken 76 simulations of isoviscous… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 70 publications
1
17
1
Order By: Relevance
“…ref. 51). Due to the dynamic nature of models driven by plate motion history, the models in this study are not strictly ‘statistically steady state’; rather, we initially generate a ‘steady-state’ condition (here termed pre-condition ) and then further condition the model with an initial plate stage (here termed plate condition ) (details given in the Supplementary Information Part 1).…”
Section: Methodsmentioning
confidence: 99%
“…ref. 51). Due to the dynamic nature of models driven by plate motion history, the models in this study are not strictly ‘statistically steady state’; rather, we initially generate a ‘steady-state’ condition (here termed pre-condition ) and then further condition the model with an initial plate stage (here termed plate condition ) (details given in the Supplementary Information Part 1).…”
Section: Methodsmentioning
confidence: 99%
“…Long-timescale mantle convection is difficult to constrain empirically and extensive use has been made of numerical modelling. Previous studies of mantle convection in both 2-dimensional and spherical geometry have shown that Earth's mantle is or has been transitionally layered about the 660 km deep Olivine phase boundary (Davies 1995;Yanagisawa et al 2010;Wolstencroft and Davies 2011;Herein et al 2013). The transitionally layered state demonstrates time dependent behavior such as mantle avalanches (Tackley et al 1993).…”
Section: Introductionmentioning
confidence: 97%
“…However, although perhaps more limited in their applicability, more established codes, which are based upon older numerical methods, remain heavily utilised within the community (e.g. Nakagawa and Tackley, 2008;Schuberth et al, 2009;Davies and Davies, 2009;Nakagawa et al, 2009;Zhang et al, 2010;Wolstencroft and Davies, 2011;Tan et al, 2011;Davies et al, 2012;Miller and Becker, 2012;Bower et al, 2013). A means to extend the lifetime and applicability of such codes is therefore highly desirable.…”
Section: R Davies Et Al: Geometric Multigrid Refinement Techniqumentioning
confidence: 99%
“…McKenzie et al, 1974;Gurnis and Davies, 1986;Davies and Stevenson, 1992;Moresi and Solomatov, 1995;Labrosse, 2002;van Keken et al, 2002;Lowman et al, 2004;King, 2009;Lee and King, 2009;Hunt et al, 2012), 3-D spherical geometry is implicitly required to simulate global mantle dynamics (e.g. Tackley et al, 1993;Bunge et al, , 1997Zhong et al, 2000;Oldham and Davies, 2004;McNamara and Zhong, 2005;Davies, 2005;Nakagawa and Tackley, 2008;Schuberth et al, 2009;Davies and Davies, 2009;Wolstencroft et al, 2009;Tan et al, 2011;Styles et al, 2011;Davies et al, 2012). However, large-scale global mantle convection models of this nature place extreme demands on computational resources.…”
Section: Introductionmentioning
confidence: 99%